Growing in the shadows of suicide - Costa, Ana Vera (2020)
Introduction: Children/adolescents mourning the death of a primary caregiver face several challenges, including bond breaking and family restructuring due to loss. The negative connotation associated with suicide loss is enhanced by stigma, increasing acceptance difficulties and feelings of isolation, abandonment, shame, and guilt in face of what happened. Objective: The aim of this study was to retrieve data on childhood bereavement due to primary caregiver suicide and explore psychopathological and psycho-affective developmental consequences of this type of grief. Methods: Literature review of articles published on PubMed database about the subject. Results and Discussion: Bereavement of a suicidal parent is associated with multiple psychopathological conditions: mood disorders, post-traumatic stress disorder, substance abuse, self-injurious behavior, suicidal behavior. Suicide and depressive disorder risk is higher when parental death occurred early in life course, with maternal suicide having greater impact. Antidepressants are more commonly used in cases of early parental death from suicide and are associated with increased hospitalizations for Major Depression and Bipolar Affective Disorder in adulthood. Consequences of parental death by suicide may be explained by several factors, as genetics, biological reactions, psychological factors originated from loss of an attachment figure, or social and environmental changes. Conclusions: Parental suicide can be impactful for children’s developmental trajectory and later functioning level. The authors alert to the need for prevention and early intervention strategies associated with this process.